2020
DOI: 10.1111/evo.14038
|View full text |Cite
|
Sign up to set email alerts
|

When does gene flow facilitate evolutionary rescue?

Abstract: Experimental and theoretical studies have highlighted the impact of gene flow on the probability of evolutionary rescue in structured habitats. Mathematical modeling and simulations of evolutionary rescue in spatially or otherwise structured populations showed that intermediate migration rates can often maximize the probability of rescue in gradually or abruptly deteriorating habitats. These theoretical results corroborate the positive effect of gene flow on evolutionary rescue that has been identified in expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 55 publications
6
34
0
Order By: Relevance
“…Indeed, there are several cases in Fiji in which small islands have distinct species from the large islands (honeyeaters, Andersen et al, 2014;monarch-flycatchers, Andersen et al, 2015;fruit-doves, Cibois et al, 2014). Despite the potential for genetic swamping, this asymmetric gene flow could also facilitate genetic rescue of small island populations in deteriorating conditions (Brown & Kodric-Brown, 1977;Tomasini & Peischl, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there are several cases in Fiji in which small islands have distinct species from the large islands (honeyeaters, Andersen et al, 2014;monarch-flycatchers, Andersen et al, 2015;fruit-doves, Cibois et al, 2014). Despite the potential for genetic swamping, this asymmetric gene flow could also facilitate genetic rescue of small island populations in deteriorating conditions (Brown & Kodric-Brown, 1977;Tomasini & Peischl, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study of insular avian gene flow found more migrants from a larger to a smaller island (Cooper & Uy, 2017). This higher rate of gene flow suggests increased genetic homogenization between insular populations and could facilitate genetic rescue of smaller populations (Bell, 2017;Brown & Kodric-Brown, 1977;Tomasini & Peischl, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…Post host-switch speciation can occur in the presence of gene flow, if specialization is adaptively favored and selection acts on many genomic regions (26,27). By promoting genomic heterogeneity and introducing beneficial mutations (28), gene flow can ameliorate lost diversity due to selection or inbreeding (29,30), both of which would impact host-switched Varroa populations. Alternatively, de novo mutation rates could contribute to population genetic variation, but our direct estimation of mutation rate did not show exceptionally high mutation rates (>8 × 10-10 per bp per generation), compared to other arthropods (31).…”
Section: Discussionmentioning
confidence: 99%
“…It equals 1 before the first environmental change takes place ( t < 0), and decreases by 1/ M after each environmental deterioration event, until it eventually hits 0, when all patches have undergone the environmental change. This setting corresponds to the one analyzed by Uecker et al (2014), and more recently by Tomasini and Peischl (2020) in the special case of just two patches. The maximum numbers of individuals that can live in a patch of a given habitat type, i.e.…”
Section: Model and Methodsmentioning
confidence: 99%
“…In fragmented environments, habitat deterioration is not necessarily synchronized across patches: there can be a transient spatially heterogeneous environment consisting of a mosaic of old- and of degraded-habitat patches, until eventually the whole environment has deteriorated. If individuals that populate different patches are able to move between those, the effect of dispersal on evolutionary rescue needs to be taken into account (Uecker et al, 2014; Tomasini and Peischl, 2020). The intensity of dispersal among patches tunes how abruptly environmental change is experienced.…”
Section: Introductionmentioning
confidence: 99%